APPLICATION OF FOREIGN EXPERIENCE IN DEVELOPMENT OF INNOVATIVE TERRITORIAL CLUSTERS IN THE RUSSIAN FEDERATION - S. Pospelov (Вестник университета, 2016)
The international experience shows that development of innovative systems and innovative processes in foreign countries is connected with clusterization policy. In the article problems of the organization, forming and development of innovative territorial clusters in the context of need of innovative development of the Russian economy are considered and generalized.